(untitled) - Widdowson, H. G. (New York, N.Y., 1999)
Professor Widdowson provides a critical review of the most prominent issues in language teaching today - among them the relevance of theoretical enquiry to practical pedagogy, and the relationship between grammar and discourse in communicative language teaching. He relates these issues to general perspectives on the nature of language and language learning
Keywords: Language and languages,Second language acquisition; Study and teaching